Metal Complexes of Adenine Azo Ligand: Synthesis, Identification and Study some of their Applications - Abd, Zaid Zuhair; Abbas, Alyaa Khider (Iraqi Journal of Science, 2024)
This scientific paper presents two novel lanthanide metal complexes [Sm (III) and Ce (IV)] synthesized through a series of reactions involving organic ligand 8-[3-(pyrazoyl)azo]adenine (PAA). Ligand (PAA) and their complexes were characterized using various analytical techniques, including C.H.N.S elemental analysis, magnetic measurement, X-ray diffraction, thermal analysis, SEM, (TGA) UV-Vis spectroscopy, FT-IR spectroscopy, and HNMR analysis. These techniques were employed to support the mode of binding and geometrical structure for ligand (PAA) and its Lanthanide (Ln) complexes. The FTIR and HNMR spectral results showed that   (PAA) acts as neutral N,N-bidentate with [Sm (III) and Ce (IV)]. The geometric shape of the synthesized Ln-complexes is octahedral. Also, TGA was used to investigate the thermal behavior of ligand and its complex. The results showed that the ligand dissociated in three steps, while the complex dissociated in five steps. This indicates that the complex is more thermally stable than the ligand, likely due to the formation of strong coordination bonds between the ligand and the metal ions. These findings can contribute to the understanding of the thermal stability of metal complexes and inform the design of new metal-based materials with desirable properties. Finally, this paper examined the antibacterial, antifungal and anticancer activities of PAA and its complexes. The results indicated that all of these compounds exhibited significant activity against bacterial and fungal pathogens, as well as cancer cells.